Reanimating the strangled rivers of Aotearoa New Zealand - Brierley, Gary J.; Hikuroa, Daniel; Fuller, Ian C.; Tunnicliffe, Jon; Allen, Kristiann; Brasington, James; Friedrich, Heide; Hoyle, Jo; Measures, Richard (WIREs Water, 2022)
Contemporary management practices have artificially confined (strangled) river systems in Aotearoa New Zealand to support intensified land use in riparian areas. These practices work against nature, diminishing the functionality and biodiversity values of living rivers, and associated socio-cultural relations with rivers. River confinement can accentuate flood risk by promoting development in vulnerable locations and limiting the flexibility to adapt to changing climate, prospectively accentuating future disasters. To date, uptake of space-to-move management interventions that seek to address such shortcomings is yet to happen in Aotearoa New Zealand. This is despite the fact that such practices directly align with Māori (indigenous) conceptualizations of rivers as indivisible, living entities. Treaty of Waitangi obligations that assert Māori rights alongside colonial rights of a settler society provide an additional driver for uptake of space-to-move initiatives. This article outlines a biophysical prioritization framework to support the development and roll out of space-to-move interventions in ways that work with the character, behavior, condition, and evolutionary trajectory (recovery potential) of each river system in Aotearoa. This article is categorized under: Water and Life > Conservation, Management, and Awareness Science of Water > Water and Environmental Change
Keywords: environment; environmental protection; mana moana; mana tupuna; mana whenua; mātauranga māori; tikanga | indigenous law; water management

Opportunities and complexities for Māori and mana whenua representation in local government - Bargh, Maria (Political Science, 2016)
In this article, I outline the existing legislative options available and rationale for M?ori representation in local government. I suggest that the arguments and rationale against M?ori representation have been exacerbated by a lack of clarity around local government?s duties and obligations stemming from the principles of the Treaty of Waitangi. In the second part of this article, I explore more recent arguments by M?ori for representation and involvement in local government decision-making on the basis of being mana whenua, which means to have territorial authority and power associated with the possession and occupation of tribal land. This argument foregrounds specific iwi (tribes) as holding territorial authority and therefore rights to representation and involvement in decision-making sourced in tikanga M?ori (M?ori law), over and above other M?ori who live in that area. I examine in detail the Rotorua District Council?s establishment of the Te Arawa Partnership Board in 2015 and argue that this Board and its first election results provide unique insights into the relationship between Te Arawa people living in and outside the district and has implications for broader conversations about the rights of M?ori living away from their tribal areas.
Keywords: kāwanatanga; local government; mana whenua; political participation; racism; representation; tikanga | indigenous law; tiriti o waitangi/treaty of waitangi; treaty obligations; treaty principles; voting